SISTEM PENDUKUNG KEPUTUSAN KINERJA KARYAWAN BUMI MANDIRI SUKABUMI MENGGUNAKAN METODE AHP - Widy Karisma; Arny Lattu; Anton Permana (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Employee performance decision support system (SPK) is very important to assist management in making the right decisions regarding employee performance evaluation. This research aims to develop an employee performance decision support system at Bumi Mandiri Sukabumi using the Analytical Hierarchy Process (AHP) method. The AHP method is used to obtain the weights of criteria and alternatives, and produce an alternative priority order. The data used in this study were obtained from employee performance evaluations at Bumi Mandiri Sukabumi in 2023. The assessment was carried out by direct interviews with superiors and included four criteria, namely work experience, education, ethics and loyalty. The results showed that work experience was ranked first with a weighted value of Work experience 0.473, Education 0.274, Eltika 0.164 and Loyalty 0.88. In addition, of the five alternative employees assessed, employees with names namely rifai ranked first, rifai 0.033780, Sabrina 0.28499, Widy 0.23530, Sarah 0.20787 in terms of performance. The developed employee performance decision support system can assist management in making more precise and accurate decisions regarding employee performance evaluation. The developed employee performance decision support system can assist management in making more precise and accurate decisions regarding employee performance evaluation.